ANALISIS PENGGUNAAN SENSOR SUHU DAN KELEMBABAN UNTUK MONITORING LINGKUNGAN GREENHOUSE BERBASIS ARDUINO - Rianti, Kurnia Paranita Kartika; Prastyo, Yogi (Universitas Islam Balitar, 2022)
Green House is a construction building that functions to manipulate environmental conditions to create the desired environmental conditions in order to optimize plant maintenance, environmental conditioning carried out in the greenhouse includes temperature and humidity regulation, soil temperature and humidity regulation and good watering. The problem that occurs is the uneven distribution of air and soil temperature and humidity in all greenhouse areas which will ultimately affect plant growth in that area. This can be overcome by adding smart devices to the greenhouse. Analysis of temperature and humidity in the greenhouse aims to maximize the microclimate for plant growth. The analysis was carried out by measuring the conditions of temperature, air humidity and soil moisture without using automatic environmental temperature and humidity control devices. Then an analysis of environmental conditions is carried out by adding sensors and adding sprayers and fans connected to sensors measuring soil and air temperature and humidity. In this study used temperature and humidity sensors air DHT11, soil moisture sensor YL 69. The sensor is connected to the Arduino UNO microcontroller to carry out commands to the sprayer and fan. Before designing an automation system, an analysis is carried out on the range of fans and sprayers used. From the analysis carried out, the greenhouse area is divided into 8 measurement lines. Based on the research that has been done, it can be concluded that by using automatic temperature and humidity control devices for air and soil, the distribution of temperature and humidity becomes more pronounced, the resulting microclimate can support plant growth. Before the automation, the distribution of the greenhouse microclimate was not evenly distributed at every point and every time, whereas after the automation, the distribution became even. Optimization can be done even better if you pay attention to the needs of plants based on the type of plant being cultivated.